Virtual skin: assessing player experience of attractiveness with the User Experience Questionnaire (UEQ) / Noraziah Mohd Razali, Azahar Harun and Ruslan Abdul Rahim - Mohd Razali, Noraziah; Harun, Azahar; Abdul Rahim, Ruslan (Faculty of Art and Design, 2021)
There are numerous subfields within visual communication, one of which is new media, alongside conventional practices such as advertising, photography, the web, animation, and signage. Blogs, social media, video games, email and the pervasiveness of smartphones have all resulted in the emergence of new media that are inextricably linked to the internet and the online environment. since the first mobile game, "Tetris", in 1994 and “Snakes" in 1997, the visual element in mobile games has evolved significantly, culminating in the modern-day mobile gaming world. These changes have involved progress from the black and white images of the early games to the variety of colours used in game visuals today and the creation of virtual goods in-app games. A skin is one of these virtual goods or items and is synonymous with a virtual appearance, outfit or cosmetic item that can be used to modify and enhance the appearance of a player's avatar. This is a cosmetic item and purely aesthetic in nature, serving no functional purpose. Among players, the desire for a skin is undeniable. Apart from the "beauty factor," another hidden value is inherent in players' perceptions of their interactions with purely aesthetic items. To determine the attractiveness of the skin in mobile games, preliminary research on skin evaluation was conducted to ascertain players' perceptions of recent virtual skins they had used in-game. The purpose of the study was to identify players’ perceptions of the attractiveness of the skin they used. To conduct the research, the Standard User Experience Questionnaire (UEQ) was used to determine the attractiveness of the skin as a virtual product. The UEQ is composed of six scales and twenty-six items that assess attractiveness on a hedonic and pragmatic level. Thirty respondents were chosen, and data analysis was performed using UEQ Data Analysis Tools. The product's benchmark was divided into five UX quality categories: excellent, good, above average, below average, and bad. The results indicate that stimulation is an excellent proxy for the UX quality of skin and efficiency is above average; meanwhile, attractiveness, perspicuity, dependability, and novelty were below average.